(untitled) (Conferencea, 2024)
This article analyzes social and political scenes in the work of Jack London, one of the realist writers, and Abdulla Kakhhar, who entered Uzbek literature as an unparalleled master of this genre with his wonderful stories and were discussed similarities and differences between their famous novels “Sarob” and “Martin Eden”.